Cooperative antitumor effect of endothelial-monocyte activating polypeptide II and flutamide on human prostate cancer xenografts - Reznikov, A.G.; Chaykovskaya, L.V.; Polyakova, L.I.; Kornelyuk, A.I.; Grygorenko, V.N. (Experimental Oncology, 2011)
Recombinant cytokine-like endothelial monocyte-activating polypeptide II (EMAP II) and antiandrogen flutamide target different mechanisms of growth of androgen-dependent prostate cancer (PC). The aim of this study was to clarify whether combined treatment with EMAP II and flutamide is more effective than monotherapy with regard to retardation of PC progression. Materials and Methods: Antitumor effects of EMAP II (10 µg/kg b.w./d, s.c., 3d), or flutamide (10 mg/kg b.w./d, per os, 3d), or their combination were studied in CBA male mice bearing human androgen-dependent PC xenografts for 7 days. Androgen-dependent phenotype of the tumors was verified in preliminary castrated mice. The xenografts were weighed and underwent a histopathologic examination. The results were compared with those of non-treated mice. Results: EMAP II and flutamide used separately inhibited growth of the xenografts by 74% and 53% respectively. Both drugs caused destructive changes in malignant epithelial cells along with leukocyte infiltration of the tumor. Combined treatment inhibited tumor growth by 85%, and was more effective than monotherapy with regard to morphological changes. Conclusions: This study demonstrates cooperative inhibitory effect of EMAP II and flutamide on growth and morphology of human PC xenografts that could represent a new modality of palliative treatment of this disease.